Character Education As A Foundation For Community Development In Doridungga Village, Donggo District, Bima Regency - Hendra, Hendra; Nurlaila, Nurlaila; Sartika, Renni; Tasrif, Tasrif; Lutfi, Muhamad; Ardyansah, Ady; Haeril, Haeril; Irfan, M.; Oktafiana, Pingkan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This Community Service Program (PPM) was carried out as an implementation of the Tri Dharma of Higher Education at Mbojo Bima University in response to the declining quality of character among the younger generation, particularly in Doridungga Village, Donggo District, Bima Regency. The growing phenomenon of moral degradation among adolescents necessitates strengthened character education through synergy between families, schools, and the community. This activity aims to enhance the knowledge, understanding, and awareness of parents and community members regarding the importance of character education as a foundation for shaping positive behavior in children. The method employed involved face-to-face counseling sessions through lectures, discussions, and question-and-answer activities, engaging 48 participants and three resource persons from Mbojo Bima University. The material presented covered the basic concepts of character education, character values, and strategies for developing character through intervention and habituation. The results indicated a high level of participant enthusiasm, as reflected by numerous questions related to the implementation of character education in daily life. Despite several challenges, such as limited time and varying levels of participant comprehension, the overall objectives of the activity were achieved. Participants demonstrated improved understanding and awareness of the importance of character education, providing a positive impact on strengthening the roles of families and communities in shaping the character of the younger generation.